Feasibility of replacing face‐to‐face with telephone interviews for the World Mental Health Qatar survey during the COVID‐19 pandemic - Salma M. Khaled (13847737) (2024)
Objectives We investigated the feasibility of replacing face‐to‐face with telephone interviews conducted as part of the World Mental Health Qatar (WMHQ) survey and discuss the main methodological changes across the two pilots that were subsequently implemented in the full‐scale WMHQ telephone survey. Methods We assessed the net mode effect by comparing the lifetime prevalence estimates of the main mental disorder classes (mood and anxiety disorders) and a number of disorders across the two survey pilots conducted prior to and post‐pandemic. Results The main differences in terms of methodology for both pilots stemmed from differences in the survey mode, including questionnaire length, study recruitment method, and fielding team size and structure. These factors influenced response rates and costs. However, the lifetime prevalence estimates and other key indicators of survey results did not differ across modes. Conclusions Our findings confirm the comparability of data collected via telephone and face‐to‐face modes, supporting the adoption of telephone surveys for future mental health studies, particularly in the context of pandemics. They also confirm the feasibility of changing or mixing modes depending on field conditions in future psychiatric epidemiological research. Other Information Published in: International Journal of Methods in Psychiatric Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/mpr.2009